Bibliometric Mapping of Green Technology Innovation in the Manufacturing Industry - Judijanto, Loso; Sumerli A., Chevy Herli; Ivander, Filbert; Salim, Brian Sebastian (West Science Interdisciplinary Studies, 2023)
This bibliometric mapping study provides a comprehensive analysis of green technology innovation within the manufacturing industry, employing quantitative methods to uncover thematic clusters, research trends, author collaborations, and research gaps. Three distinct thematic clusters—Sustainable Manufacture, Enterprise, and Challenge—emerge, each offering insights into prevalent terms and themes. The analysis of research trends reveals the evolution of key terms over time, highlighting emerging topics. Author collaboration mapping identifies influential researchers and collaborative networks, facilitating interdisciplinary partnerships. The study's implications extend to resource allocation, policy formulation, and industry best practices, emphasizing academia's pivotal role in sustainable manufacturing. Overall, this research serves as a roadmap for future endeavors, fostering collaboration, informing policy, and driving innovation in green technology within the manufacturing sector.